Accounting and Corporate Deception: A Global and Indian Perspective on ‎Forensic Accounting Interventions - Rani , Dr. Barkha; Das , Suman; Rana , Dr. Saurabh; Bishnoi , Dr. Narender Kumar; Prasad , Mahaveer (International Journal of Accounting and Economics Studies, 2025)
Over the past decade, financial fraud has transformed from isolated misconduct to intricate, cross-border networks exploiting systemic weaknesses in governance, technology, and regulation. ‎Traditional audit and compliance solutions, which are reactive and compartmentalized, are falling ‎behind the adaptive and scalable nature of fraud. It is challenging to discern between deliberate ‎fraud and legitimate transactions due to sophisticated tactics like smart contract attacks and ‎synthetic identities. As a front-line defence, forensic accounting necessitates a proactive, ‎intelligence-driven strategy that combines knowledge of finance, cyber, regulations, and risk. ‎Despite legislative improvements, India’s system is reactive rather than preventive due to large ‎gaps in enforcement, coordination, and specialized capability. Closing this gap requires ‎incorporating forensic methods into corporate governance and encouraging shareholder ‎participation. Advanced technologies like blockchain traceability and real-time surveillance are ‎essential to this evolution. The future of fraud prevention depends on institutions’ capacity to ‎promptly identify and eradicate emerging risks. Forensic accounting must evolve into a core pillar ‎of financial oversight to safeguard systemic integrity in an era of engineered deception‎.